Respuestas

2013-10-06T08:49:42+02:00
Prueba 1

p q r  ((p <-> q) -> r)
-----------------------
v v v    v  v  v  v  v
v v F    v  v  v  F  F
v F v    v  F  F  v  v
v F F    v  F  F  v  F
F v v    F  F  v  v  v
F v F    F  F  v  v  F
F F v    F  v  F  v  v
F F F    F  v  F  F  F
                 (1)

p q r   (((p & q) -> r)  &  ((~p & ~q) -> r))
---------------------------------------------
v v v      v v v  v  v   v    F  F F   v  v
v v F      v v v  F  F   F    F  F F   v  F
v F v      v F F  v  v   v    F  F v   v  v
v F F      v F F  v  F   v    F  F v   v  F
F v v      F F v  v  v   v    v  F F   v  v
F v F      F F v  v  F   v    v  F F   v  F
F F v      F F F  v  v   v    v  v v   v  v
F F F      F F F  v  F   F    v  v v   F  F
                        (2)

(1) = (2) => (p <-> q) -> r <-> (p & q -> r) & ( ~p & ~q -> r)

Prueba 2:

 a) |- ((P <-> Q) -> R) -> (P & Q -> R) & (~P & ~Q -> R)


 b) |- (P & Q -> R) & (~P & ~Q -> R) -> ((P <-> Q) -> R).


 c) |- ((P <-> Q) -> R) <-> (P & Q -> R) & (~P & ~Q -> R)


a) |- ((P <-> Q) -> R) -> (P & Q -> R) & (~P & ~Q -> R)